Persepsi Guru Terhadap Implementasi Kurikulum Merdeka Pada Sekolah Dasar - Umar Umar; Me Indra Jayanti; Nurfidianty Annafi; Lukman Lukman (Jurnal Studi Guru dan Pembelajaran, 2024)
The success of implementing the curriculum in schools is very dependent on the teacher's perception in accepting and understanding the content of implementing the independent curriculum within the scope of the educational unit. So it is important to know the teacher's perception index in implementing the independent curriculum in elementary schools. This research aims to analyze the teacher's perception index regarding the implementation of the independent curriculum in elementary schools in Bima. This research method was carried out using a survey approach. The main sample of this research was 32 elementary school class teachers who implemented an independent curriculum. The data analysis technique was carried out descriptively. The results of the research reveal that elementary school teachers in Bima City can generally understand the theoretical realm and technical framework in implementing the Independent Curriculum. This is evidenced by the positive perception of teachers regarding the implementation of the independent curriculum in elementary schools, including; 62.5% of teachers think that the concept of an independent curriculum for elementary school students is in accordance with the theoretical basis of education. The remaining 37.5% felt that the independent curriculum concept was very suitable for elementary school students in Bima. It was identified that 69% of teachers were strongly influenced by internal factors and 31% were influenced by external factors in implementing the independent primary school curriculum. In another aspect, as many as 43.8% thought that discussion activities were initiated by teachers and the school, which also influenced the optimization of the implementation of the independent curriculum in elementary schools in Bima.